Empowering Clinician Education With Patient‐outcome Feedback. Issue 4 (6th July 2020) - Iserson, Kenneth V.
Abstract: Emergency physicians (EPs) often lack the information they need about their patients' outcomes so that they can both optimally adjust and refine their diagnostic and treatment processes and recognize their clinical errors. Patient‐outcome feedback (POF) provides that information by informing clinicians about a patient's clinical course after that clinician's evaluation and treatment. This feedback may encompass the period after the EP has transferred a patient's care to another EP or after the patient has left the ED or hospital. EPs obtain POF through various active and passive methods, depending on their institutional and medical record systems. Active methods require that clinicians or others spend time and effort acquiring the information; passive methods deliver it automatically. POF is an excellent performance‐based measurement that helps clinicians to stimulate their learning and to build their own validated mental library of outcomes with which to make clinical decisions, i.e., heuristics and System 1 thinking. POF offers especially useful feedback about patients who have been admitted, were referred to specialists, had major interventions, had potentially significant tests pending on discharge, or were handed off to another EP. The current health care system makes it difficult for EPs to discover their patients' outcomes, squandering significant educational opportunities. Three stimuli to improve this situation would be to require EPs to receive passive POF as part of hospital accreditation, for reviewing POF to be classified as a Category 1 Continuing Medical Education activity, and to reimburse clinicians for learning activities related to POF. Research indicates that our health care institutions and systems would be well served to provide clinicians with ongoing automatic information about their patients' outcomes.